Sexual behavior and self-declaration of sexual orientation among people 18-64 years in Brazil: results from the Knowledge, Attitudes, and Practices survey, 2013 and the National Health Survey, 2019 - Célia Landmann Szwarcwald; Ana Roberta Pati Pascom; Paulo Roberto Borges de Souza Júnior; Giseli Nogueira Damacena; Euclides Ayres Castilho (BMC, 2023)
Abstract Background Population surveys involving the monitoring of high-risk sexual behavior have been recognized as important public health tools to control the HIV epidemic and other sexually transmitted infections (STIs). Methods Using data from the Knowledge, Attitudes, and Practices survey (PCAP-2013) and from the National Health Survey (PNS-2019), indicators of sexual behavior were compared according to sociodemographic characteristics among individuals aged 18-64 years, including size (%) estimates of men who have sex with men (MSM) and women who have sex with women (WSW). Specifically, the PNS-2019 prevalence estimates of homosexual, bisexual, heterosexual males and females were compared with those from the PCAP-2013. To compare PCAP and PNS proportional distributions, the Pearson's chi-square test, adjusted by the Rao-Scott's correction, was applied. Results Size (%) estimates of MSM and WSW obtained by direct questions from the PCAP-2013, showed higher homosexuality prevalence estimates than those resulting from the PNS-2019 self-declared sexual orientation. Significant differences were found between the MSM proportions according to the PCAP-2013 (3.7%; 95% CI 3.1-4.4%) and to the PNS-2019 (2.2%; 95% CI 1.9-2.5), and between the WSW proportions (4.6%; 95% CI 4.0-5.4%) and (2.1%; 95% CI 1.8-2.4), respectively. Results from both surveys showed MSM and WSW prevalence estimates increase with educational level, decrease with age, and is larger among people who do not live with partner, live in urban areas and in state capitals. Regarding condom use at last sexual intercourse, no differences between the PCAP-2013 and the PNS-2019 estimates were found at the national level, but significant improvements were found for MSM, people aged 18-24 and 25-34 years, and individuals not living with a partner. Conclusions The underestimation of MSM and WSW prevalence by self-declared sexual orientation suggests that sexual minorities face many difficulties related to disclosing their sexuality and reinforces the importance of developing public health interventions for changing population attitudes and promoting sexual orientation disclosure. Moreover, the low use of condoms in both surveys (PCAP-2013 and PNS-2019) carried out 6 years apart highlights the need of public policies to expand prevention strategies for HIV infection and other STIs.